Digital media in early childhood: risk factors for online harm and psychosocial correlates - Gath, Megan; Swit, Cara (Frontiers in Developmental Psychology, 2024)
IntroductionEarly and middle childhood are times of rapid development, and critical periods for laying the foundations of life-long trajectories of socioemotional well-being. High levels of screen media use are of growing concern to parents, health professionals, and researchers, given the increasing body of research demonstrating detrimental impacts of excessive screen use in young children. One particular consequence is the risk that children encounter online content or experiences that are upsetting or distressing, including exposure to inappropriate or adult content, cyberbullying, and interactions with strangers that they don't know.MethodsThis research examined experiences of online harm reported in a sample of 8-year-old children, with a focus on identifying risk factors and psychosocial correlates of online harm. Data for this study were collected from children and their mothers as part of the prospective longitudinal Growing Up in New Zealand (GUiNZ) study (n = 4,920 children with data at age 8). Children were assessed at 4.5-years-old and 8-years-old.ResultsThe findings of this research indicate that approximately a quarter of New Zealand children have experienced online harm (that is, have encountered online content that worried, upset, or bothered them) by the age of 8. Our analysis indicates that children with behavioral difficulties are at greater risk of online harm, as are children with more personal devices. Experiences of online harm were found to be negatively associated with child self-worth and positively associated with depressive symptoms.DiscussionFindings highlighting the critical importance of considering online harm as a contributing factor to child and youth well-being and mental health in our media-saturated world. Our results also point to practical solutions for parents, such as limiting the number of personal media devices that children have in early and middle childhood.